RORγt Mediates Angiotensin II‐Induced Pressor Responses, Microglia Activation, and Neuroinflammation by Disrupting the Blood–Brain Barrier in Rats - Yang Yu; Baojian Xue; Lei Tong; Alexander G. Bassuk; Alan K. Johnson; Shun‐Guang Wei (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The RORγt (nuclear receptor retinoid‐related orphan receptor γt) has been identified as a master transcription factor critical for the differentiation of T helper 17 cells, the primary source of IL‐17A (interleukin‐17A). We previously demonstrated that IL‐17A promotes neuroinflammation and sympathetic excitation, contributing to cardiac dysfunction in heart failure and angiotensin II (ANG II)‐induced hypertension. The present study sought to determine whether inhibiting RORγt, thereby reducing IL‐17A production, could attenuate microglial activation, neuroinflammation, and sympathetic excitation by preserving the integrity of the blood–brain barrier (BBB) in ANG II‐induced hypertensive rats. Methods Rats underwent a 2‐week subcutaneous infusion of ANG II, with concurrent daily subcutaneous administration of the RORγt inhibitor digoxin or vehicle. Results Compared with controls, ANG II‐infused rats exhibited elevated IL‐17A levels in both the periphery and brain, along with increased blood pressure and sympathetic tone—effects that were significantly attenuated by inhibiting RORγt with digoxin. ANG II‐infused rats also displayed heightened BBB permeability, decreased expression of the BBB regulator Mfsd2a (major facilitator superfamily domain‐containing protein 2a), increased caveolar transcytosis, and degradation of tight junction proteins in BBB endothelial cells within the hypothalamic paraventricular nucleus, a key autonomic regulatory brain center, all of which were alleviated by digoxin. Additionally, ANG II‐infused rats showed marked microglial activation and elevated expression of proinflammatory cytokines within the paraventricular nucleus, both of which were mitigated by digoxin. Conclusions These findings suggest that RORγt inhibition reduces neuroinflammation and sympathetic activation to ameliorate ANG II‐induced hypertension, likely by mitigating IL‐17A‐induced BBB disruption and microglial activation in the paraventricular nucleus.